Bilateral Trigeminal Neuralgia Refractory to Medical Therapy: Importance of A Multi-Therapeutic Approach - Fraioli, Mario Francesco; Lisciani, Damiano; Pagano, Andrea; Fraioli, Chiara (Archives of Case Reports, 2025)
Bilateral trigeminal neuralgia refractory to medical therapy is a rare occurrence and it is mandatory to choose therapeutic procedures minimizing possible bilateral sensitive deficit due to the employment of bilateral mininvasive ablative techniques. A patient affected by bilateral trigeminal neuralgia refractory to medical therapy secondary to multiple sclerosis is presented. Multiple therapeutic tools were employed in this challenging pathology. The second and third left trigeminal divisions were involved by the neuralgia, while the third division was involved in the right facial side. Controlled radiofrequency thermocoagulation was employed for the isolated right third division, then radiosurgery was conducted for the left hemifacial side. After one month, because of the persistence of pain attacks of the left second trigeminal division, peripheral authorizations were performed. Control of pain, with the withdrawal of medical therapy (BNI scale class I), was achieved in this patient with a multi-therapeutic approach. Radiofrequency thermorizotomy was performed for the right third division because neuralgia was very acute, and immediate pain relief was achieved. Pain in the left third trigeminal division regressed after radiosurgery, while pain in the left second division continued after radiosurgery, then peripheral alcoholization was performed with pain control. Bilateral trigeminal neuralgia refractory to medical therapy should be treated by the dedicated neurosurgeon, avoiding bilateral ablative techniques for the same division and using neurosurgical techniques according to the trigeminal division interested by the neuralgia and according to the intensity of pain.